Relapsed or primary refractory AML: moving past MEC and FLAG-ida. Issue 2 (March 2020) - Koenig, Kristin; Mims, Alice
Abstract : Purpose of review: Treatment of relapsed and refractory acute myeloid leukemia (AML) is still very challenging, with poor response rates and low chance for cure. This is especially true when treating patients who are elderly, have multiple comorbidities, or who are too unfit for traditional salvage chemotherapy regimens. Recent findings: Recently, advances in the treatment of relapsed/refractory AML utilizing novel chemotherapy combinations, hypomethylating, and targeted therapies have shown promising results. Summary: Several early-phase studies with novel targeted therapy combinations have demonstrated encouraging results warranting larger, comparative studies. This has expanded the access of treatment for patients with relapsed/refractory AML who cannot receive traditional salvage chemotherapy. These newer treatments have the potential to outperform traditional chemotherapy as well.